1933
DOI: 10.6028/jres.010.035
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and crystallization of pure ether-soluble rubber hydrocarbon: Composition, melting point, and optical properties

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1934
1934
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In 1933 and 1934, Smith et al (260,261,262) prepared pure rubber hydrocarbon, crystallized it, and then separated it into sol and gel by extraction with ethyl ether; they also succeeded in crystallizing the sol and gel fractions, and examined their properties. Staudinger (22) fractionated rubber by diffusion, and found that the molecular weights of the four fractions differed only slightly.…”
Section: B Rate-of-solution (Diffusion) Methodsmentioning
confidence: 99%
“…In 1933 and 1934, Smith et al (260,261,262) prepared pure rubber hydrocarbon, crystallized it, and then separated it into sol and gel by extraction with ethyl ether; they also succeeded in crystallizing the sol and gel fractions, and examined their properties. Staudinger (22) fractionated rubber by diffusion, and found that the molecular weights of the four fractions differed only slightly.…”
Section: B Rate-of-solution (Diffusion) Methodsmentioning
confidence: 99%
“…To detect these reactions by chemical means adequately expresses the structure (or chemical properties) of highly purified rubber (12). It predicts carbon-hydrogen ratios that are checked by experiment within a few tenths of a per cent (35) and unsaturation values that are verified within about one-half per cent, as well as the approximate composition of reaction products with ozone, sulfur, chlorine, etc. It has been assumed (13) that if n is large, as osmotic pressure, viscosity (36), and ultracentrifuge (5) tests show it to be, then the question of whether the chains form closed rings or are open at the ends is not of great significance.…”
mentioning
confidence: 76%
“…This formula does not explain a number of different properties of crude rubber which are of interest and importance to rubber technologists, such as the observed dipole moments of rubber in solutions (30), the effect of the drying of rubber on the viscosity of its solutions (23), or the effect of traces of piperidine on the viscosity. Nor does it explain why purified crude rubber can be separated by diffusion processes into two more or less definite fractions-the sol and gel rubbers-which have about the same ultimate chemical analysis (35); nor why the gel rubber eventually goes into solution if given enough time in contact with air; nor why, when solutions of gel rubber are cooled, the crystals formed have different melting points ( -1.5°to +10°C. or +29,3°t o +50°F.)…”
mentioning
confidence: 99%
“…In the determination of the constitution and structure of a molecule and also for identification of a compound or mixture, a total quantitative analysis of all the elements present often gives valuable information. Smith, Saylor, and Wing analyzed puri-fied natural-rubber hydrocarbon (194,237) and found that the sum of the carbon and hy-drogen totals very close to 100%; this indicates the presence of very little, if any, combined oxygen. It is unfortunate that at that time there was no reliable method for an accurate direct determination of oxygen.…”
Section: Elemental Analysismentioning
confidence: 99%